RIG-I activation is critical for responsiveness to checkpoint blockade - Heidegger, Simon; Wintges, Alexander; Stritzke, Florian; Bek, Sarah; Steiger, Katja; Koenig, Paul-Albert; Goettert, Sascha; Engleitner, Thomas; Oellinger, Rupert; Nedelko, Tatiana; Fischer, Julius C.; Makarov, Vladimir; et al. (Science immunology, 2019)
Achieving durable clinical responses to immune checkpoint inhibitors remains a challenge. Here, we demonstrate that immunotherapy with anti-CTLA-4 and its combination with anti-PD-1 rely on tumor cell-intrinsic activation of the cytosolic RNA receptor RIG-I. Mechanistically, tumor cell-intrinsic RIG-I signaling induced caspase-3-mediated tumor cell death, cross-presentation of tumor-associated antigen by CD103+ dendritic cells, subsequent expansion of tumor antigen-specific CD8+ T cells, and their accumulation within the tumor tissue. Consistently, therapeutic targeting of RIG-I with 5′-triphosphorylated RNA in both tumor and nonmalignant host cells potently augmented the efficacy of CTLA-4 checkpoint blockade in several preclinical cancer models. In humans, transcriptome analysis of primary melanoma samples revealed a strong association between high expression of DDX58 (the gene encoding RIG-I), T cell receptor and antigen presentation pathway activity, and prolonged overall survival. Moreover, in patients with melanoma treated with anti-CTLA-4 checkpoint blockade, high DDX58 RIG-I transcriptional activity significantly associated with durable clinical responses. Our data thus identify activation of RIG-I signaling in tumors and their microenvironment as a crucial component for checkpoint inhibitor-mediated immunotherapy of cancer.
CRIS-Team Scopus Importer:2023-03-23